Intraoperative glucose management in children < 1 year or < 10 kg: an observational study. (6th October 2017) - Bester, K.; Pretorius, T.
Abstract: Background: Infants may be at risk of hypoglycaemia in the perioperative period. Current evidence has led to the global use of maintenance fluid with low-concentration dextrose in these patients. This study aimed to analyse the current practice of anaesthetists in the authors' institution with regard to blood glucose management, and to assess its adequacy. Methods: Ninety-nine patients under one year of age, or less than 10 kilograms, who required anaesthesia were enrolled. The intraoperative management of intravenous dextrose administration and blood glucose monitoring was at the discretion of the attending anaesthetists. Data collected included patient demographics, period of starvation, dose of dextrose administered and blood glucose measurements taken. Results: Nine infants had at least one glucose value lower than 3.7 mmol/l at any time during the procedure, while all received intravenous dextrose intraoperatively. The hypoglycaemic episode occurred on initial measurement (start of surgery) in five infants and later on in the procedure in four infants. This subgroup had an average age of 1.5 months, and average weight of 2.9 kg. Seven of these infants had significant co-morbidities and/or prematurity and low birthweight. Conclusions: The findings indicate that anaesthetists adhere to current recommendations regarding glucose management, and confirmed the safety of intraoperative administration of 0–2.5% dextrose in isotonic solution to healthy infants. The authors' observations also emphasised that smaller infants and those with significant co-morbidities are at particular risk of developing hypoglycaemia, despite preoperative and intraoperative dextrose administration. It remains important to check glucose levels in patients at risk of hypoglycaemia.